PKM PENGEMBANGAN COMMUNITY BASED TOURISM DI DESA SUKACAI KABUPATEN SERANG BANTEN - Irwan Sukmawan; Ferdiansyah Nugraha Putra; Ali Fajri; Kisti Aprianti Purnama; Siti Laelatul Hamdiah; Siti Sumiati Dewi (Indonesian Collaboration Journal of Community Services, 2021)
Sukacai Village is one of the villages in the Baros District, Serang Regency, Banten Province. The problem that occurs is the economy of rural communities with a livelihood as farmers. The natural potential that is owned in the form of the abundance of water flow from Mount Karang does not necessarily make the area fully utilized. Steps to develop a tourist village with its natural resources need to be carried out with the concept of Community Based Tourism. So that the surrounding community can participate and improve their economy from Sukacai Village tourism